If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+8=2x(2x-8)
We move all terms to the left:
4x+8-(2x(2x-8))=0
We calculate terms in parentheses: -(2x(2x-8)), so:We get rid of parentheses
2x(2x-8)
We multiply parentheses
4x^2-16x
Back to the equation:
-(4x^2-16x)
-4x^2+4x+16x+8=0
We add all the numbers together, and all the variables
-4x^2+20x+8=0
a = -4; b = 20; c = +8;
Δ = b2-4ac
Δ = 202-4·(-4)·8
Δ = 528
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{528}=\sqrt{16*33}=\sqrt{16}*\sqrt{33}=4\sqrt{33}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(20)-4\sqrt{33}}{2*-4}=\frac{-20-4\sqrt{33}}{-8} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(20)+4\sqrt{33}}{2*-4}=\frac{-20+4\sqrt{33}}{-8} $
| -6(4x-5)+5(5x-3)-2=6-7 | | 180-x=3×(90-x)+30 | | 2/h-1/3h+11=8 | | 6x-1/6=9 | | x-16x+3x=180 | | 3/5=2x-6/3+x/5 | | x+30/8=1/4x | | 13z-8z=20 | | -131=22x+45 | | -6x-8=3x+5 | | 4x+1+47=180 | | 3w=-27+12w | | 19-3(a-6)-18=66 | | 6x(-12/3)+4=18/x | | 6(x-3)^2=0 | | (-3-4i)-(-3+5i)=0 | | 4x+3=2x(2x+3) | | Y=3/2x-13/2 | | -30=-8x-14 | | x^2-16x-3x=180 | | 4K-4+3k=5k+16 | | 8-4a=12 | | x^2-1=-x^2+3 | | 116=17+11x | | X+1-4x=-2x-17+6-5x | | 7x+2=-58 | | 3(g+6)=0 | | F(2)=x^2+2x-5 | | x^2-16x+3x=180 | | 3(4x+5)=-31+10 | | 5(3x)-4(2x-3)=4(x+3)+1 | | 17+11z=116 |